Funding Liquidity, Market Liquidity and the Cross-Section of Stock Returns - Jean-Sébastien Fontaine; René Garcia; Sermin Gungor (Bank of Canada, 2015)
Following theory, we check that funding risk connects illiquidity, volatility and returns in the cross-section of stocks. We show that the illiquidity and volatility of stocks increase with funding shocks, while contemporaneous returns decrease with funding shocks. The dispersions of illiquidity, volatility and returns widen following funding shocks. Funding risk is priced, generating a returns spread of 4.25 percent (annually) between the most and least illiquid portfolios, and of 5.30 percent between the most and least volatile portfolios. Estimates are robust using mimicking portfolio returns, alternative portfolio sorts, traditional test assets, other risk factors, monthly returns or quarterly returns.
Keywords: E43; H12; 330; Asset pricing; Financial markets